2015
DOI: 10.4238/2015.august.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between natriuretic peptide receptor C (NPR3) gene polymorphisms and hypertension in the Dai people of China

Abstract: ABSTRACT. Hypertension affects one-fifth of the world population. Genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) that correlated with hypertension in large samples. However, the genetic mutations leading to hypertension might differ among various populations, as they have different origins and are subjected to different environmental pressures. Therefore, additional studies are urgently needed to verify the GWAS findings across different populations. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…12 Increase in circulating ANP/BNP levels can lead to decrease in BP. 21 Studies have also showed an association between NPR3 polymorphism and BP level in type 2 diabetes. NPR-C is detected in the heart, lung, kidney, adrenal, placenta, cerebral cortex and cerebellum, and vascular endothelial cells.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…12 Increase in circulating ANP/BNP levels can lead to decrease in BP. 21 Studies have also showed an association between NPR3 polymorphism and BP level in type 2 diabetes. NPR-C is detected in the heart, lung, kidney, adrenal, placenta, cerebral cortex and cerebellum, and vascular endothelial cells.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…It was later verified that the rs1173766 polymorphism was associated with decreased risk of hypertension. 21 Studies have also showed an association between NPR3 polymorphism and BP level in type 2 diabetes. 22 Recently, it was observed that rs2270915 (A/G, Asn521Asp) polymorphism was associated with DBP, but not circulating levels of NPs.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…More interesting findings were obtained for the NPRC gene encoding the NP clearance receptor. In fact, in two large studies, a gene-centric array and a GWA study identified few blood pressure loci, including one containing NPRC [44,47]. A small case-control association study, utilizing SNPs belonging to NPRC, detected an association with hypertension and even with family history of hypertension [48].…”
Section: Role Of Other Components Of the Np Familymentioning
confidence: 99%
“…According to the Chinese Hypertension League 2009 report, the prevalence of hypertension in the Chinese population is high, affecting one out of five individuals, i.e. >2 billion (1). In the kidney, dopamine receptors serve a pivotal role in blood pressure regulation.…”
Section: Introductionmentioning
confidence: 99%